Роль інформаційних чинників в контексті активізації транскордонного співробітництва регіонів - Корольчук, Л. В.; Korolchuck, L. (Східноєвропейський національний університет імені Лесі Українки, 2013)
This article investigates the shortcomings of information support of cross-border cooperation, studied information mentioned factors in the process of activation of cross-border regions.
The role of information factors in the context of intensified cross-border regional cooperation
Л. В. Корольчук, к.екон.н., доц. кафедри економічної теорії та міжнародної економіки Луцького національного технічного університету (Україна, м.Луцьк)
Keywords: cross-border cooperation; cross-border region; cross-border cluster information factor